2002
DOI: 10.1902/jop.2002.73.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recombinant Human Bone Morphogenetic Protein‐2/Absorbable Collagen Sponge (rhBMP‐2/ACS) on Healing in 3‐Wall Intrabony Defects in Dogs

Abstract: Surgical implantation of rhBMP-2/ACS may be used safely to support regeneration of alveolar bone in intrabony periodontal defects in dogs without aberrant events such as root resorption or ankylosis complicating the regenerative procedure. rhBMP-2/ACS does not appear to have a significant effect on cementum regeneration and formation of a functional periodontal ligament in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
133
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(144 citation statements)
references
References 25 publications
6
133
0
2
Order By: Relevance
“…It was reported that at approximately 6 weeks, a considerable amount of new bone fill was obtained [27]. Choi et al [28], reported that no differences in bone regeneration by Bone Morphogenic Protein (BMP) were noted between an 8-and 24 week interval, hence in this study we selected 12 weeks to evaluate the healing.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that at approximately 6 weeks, a considerable amount of new bone fill was obtained [27]. Choi et al [28], reported that no differences in bone regeneration by Bone Morphogenic Protein (BMP) were noted between an 8-and 24 week interval, hence in this study we selected 12 weeks to evaluate the healing.…”
Section: Discussionmentioning
confidence: 99%
“…Cementum regeneration was also stimulated by rhBMP-2, although not significantly in some reports [104,107,108]. Ankylosis was also occasionally reported to affect periodontal regeneration associated with rhBMP-2 treatment [102,103,109].…”
Section: Growth Factor Applications For Oral and Periodontal Tissue Ementioning
confidence: 96%
“…BMPs -2, -4, -7 and -12 have all been evaluated for periodontal and peri-implant bone regeneration [67]. From this group of proteins, BMP-2 has been the most studied for bone and periodontal regenerative treatment [101][102][103][104][105][106].…”
Section: Growth Factor Applications For Oral and Periodontal Tissue Ementioning
confidence: 99%
“…1 But some studies have demonstrated that rhBMP-2 has limited regenerative ability and results in a deranged periodontal relationship, with complications such as ankylosis and root resorption. 2,3 It has been suggested that the incidence of the ankylosis relationship between the components of the regenerated periodontal apparatus and the extent of root resorption positively correlates with the dose of rhBMP-2. 4 Therapy with rhBMP-2 is limited by protein degradation and inactivation.…”
Section: Introductionmentioning
confidence: 99%